2015
DOI: 10.1017/s0954422415000050
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and pharmacological compounds altering intestinal calcium absorption in humans and animals

Abstract: The intestine is the only gate for the entry of Ca to the body in humans and mammals. The entrance of Ca occurs via paracellular and intracellular pathways. All steps of the latter pathway are regulated by calcitriol and by other hormones. Dietary and pharmacological compounds also modulate the intestinal Ca absorption process. Among them, dietary Ca and P are known to alter the lipid and protein composition of the brush-border and basolateral membranes and, consequently, Ca transport. Ca intakes are below the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 225 publications
(235 reference statements)
0
26
1
Order By: Relevance
“…The intestinal Ca 2+ absorption is an active process (ATP dependent) that mainly occurs in the small intestine, which is responsible for approximately 90% of overall Ca 2+ absorption[62]. The sojourn time in each intestinal segment and the Ca 2+ solubility are important factors affecting the intestinal Ca 2+ absorption.…”
Section: Mechanisms Of Intestinal Calcium Absorptionmentioning
confidence: 99%
“…The intestinal Ca 2+ absorption is an active process (ATP dependent) that mainly occurs in the small intestine, which is responsible for approximately 90% of overall Ca 2+ absorption[62]. The sojourn time in each intestinal segment and the Ca 2+ solubility are important factors affecting the intestinal Ca 2+ absorption.…”
Section: Mechanisms Of Intestinal Calcium Absorptionmentioning
confidence: 99%
“…30 Moreover, children with low calcium intakes also reduce their renal excretion of calcium. 30 Calcium requirements vary depending on dietary factors, such as the intake of vitamin D, 31 sodium, 4 and caffeine 32 the presence of molecules modifying intestinal calcium absorption, such as lactose 33 and other factors, such as physical activity. 4,5 Calcium excretion increases with sodium intake because these minerals share some of the same transport systems in the proximal tubule.…”
Section: How Much Is Adequate Calcium?mentioning
confidence: 99%
“…Using streptozotocin (40 mg/kg for 5 consecutive days) treated DBA/2J mice, Zhang et al [ 66 ] demonstrated that FLL-WF inhibited hypercalciuria and improved trabecular bone microstructures by increasing serum levels of PTH and fibroblast growth factor-23 (FGF-23), and upregulating mRNA expression of TRPV6 and CaBP-9k in the duodenum as well as decreasing mRNA and protein expression of calcium-sensing receptor (CaSR) in the kidney of diabetic mice. It is well known that PTH stimulates transcription and secretion of FGF-23, which further increases circulating Ca level [ 82 , 83 , 84 ]. Additionally, CaSR serves as a sensor controlling extracellular calcium homeostasis and may have an inhibitory effect on PTH secretion [ 85 ].…”
Section: Anti-bone Resorption and Pro-anabolic Activities Of mentioning
confidence: 99%